2015
DOI: 10.1113/jp270645
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal maturation of GABAergic modulation of sensory inputs onto lateral amygdala principal neurons

Abstract: Key pointsr Throughout life, fear learning is indispensable for survival and neural plasticity in the lateral amygdala underlies this learning and storage of fear memories.r During development, properties of fear learning continue to change into adulthood, but currently little is known about changes in amygdala circuits that enable these behavioural transitions.r In recordings from neurons in lateral amygdala brain slices from infant up to adult mice, we show that spontaneous and evoked excitatory and inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 86 publications
(114 reference statements)
9
21
0
Order By: Relevance
“…Furthermore, different internal solutions can also alter intracellular enzymatic activity, such as protein kinase A (Vargas et al, 1999). Another more likely possibility is that adult BLA pyramidal neurons have a more complex dendritic arborization and/or spine density (Bosch and Ehrlich, 2015), which could be better detected with the K-gluconate internal. While the reasons for this observation are not clear, these data suggest that differences in ion channels/conductances may exist in BLA pyramidal neurons across development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different internal solutions can also alter intracellular enzymatic activity, such as protein kinase A (Vargas et al, 1999). Another more likely possibility is that adult BLA pyramidal neurons have a more complex dendritic arborization and/or spine density (Bosch and Ehrlich, 2015), which could be better detected with the K-gluconate internal. While the reasons for this observation are not clear, these data suggest that differences in ion channels/conductances may exist in BLA pyramidal neurons across development.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why blockade of GABA receptors does not cause an increase in the number of active LAT neurons in adult rats (although there is a trend in this direction). Possible explanations may include additional sources of regulation (eg greater contribution of h channels, SK channels, GABA b receptors; Ehrlich et al, 2012;Bosch and Ehrlich, 2015) that suppress neuron firing even when GABA A receptors are blocked.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the contribution of PPD by GABA B receptors may be due primarily to activation of GABA B receptors in infancy, whereas PPD in older animals is only partially controlled by GABA B receptors. Moreover, Bosch and Ehrlich () found that presynaptic GABA B receptors, which are present on sensory inputs to LA principal neurons, are activated as early as P8. Finally, tonic presynaptic control of IPSCs and excitatory postsynaptic currents (EPSCs) in the LA appears to be mediated by GABA B receptors and is likely permitted by ambient GABA that also emerge in adolescence (Bosch and Ehrlich, ).…”
Section: Modulation Of Gabaa Receptor‐mediated Inhibitory Synaptic Trmentioning
confidence: 99%